HUBUNGAN ANTARA DISIPLIN KERJA DENGAN KUALITAS PELAYANAN PEGAWAI PADA KANTOR KELURAHAN LOA BAKUNG KECAMATAN SEI KUNJANG KOTA SAMARINDA - ., Norwansyah (PREDIKSI, 2014)
The Relationship Between Service Quality And Work Discipline Officers On Neighborhood Offices Of The Loa Daffodils Subdistrict Sei Kunjang Samarinda. This research aims to find out if Work Discipline had a positive relationship to quality Service Officer At The Kelurahan Loa Daffodils Subdistrict Sei Kunjang Samarinda.The results showed that there is a positive and significant relationship between variables Work Discipline with the variable quality of Service Employees At the Office of the Administrative law of attraction Sub Lilies Sei Kunjang Samarinda..  It can be noted from the results of statistical tests in which the correlation coefficient (r) is equal to 0,587, which means there are ongoing and positive relationship between the two variables.Meanwhile, the results of the test t (t-test) shows that the resulting empirical t is $ 4,183.  These results are compared with the prices of critical tables t for n-2 was 1,734.  This means there is a significant relationship between the variables Work Discipline against officers of the service quality.  Thus it can be said that the purpose of this research can be achieved, the problems can be solved and hypothesis to be proved.